South Sumatra Capital Expenditure Budget Determinants: What Factors Influence? - Pratiwi, Azhara Oktavianita; Sari, Imelda (Research of Accounting and Governance, 2025)
The purpose of this study is to examine the impact of economic growth, fluctuations in local revenue, general allocation funds, and special allocation funds on capital expenditures. The sample consists of 17 observations from South Sumatra’s Regency/City governments (13 Regencies and 4 Municipalities) during 2018–2020. Secondary data were obtained from the Republic of Indonesia Financial Audit Agency (BPK RI). Data on Gross Regional Domestic Product (PDRB) and Regional Revenue and Expenditure Budgets (APBD) were sourced from Regional Government Financial Reports (LKPD). Quantitative analysis techniques were employed. The results show that fluctuations in Regional Original Income and Special Allocation Funds significantly influence Capital Expenditures. However, Economic Growth and General Allocation Fund fluctuations do not impact Capital Expenditures. Managerially, positive economic growth can increase regional income, enabling higher capital expenditure. Fluctuations in General Allocation Funds may affect budget stability, requiring strategies to manage uncertainties.